The emerging role of exercise preconditioning in preventing skeletal muscle atrophy - Zhou, Xu; Li, Shiming; Wang, Lu; Wang, Jun; Zhang, Peng; Chen, Xiaoping (Frontiers in Physiology, 2025)
Skeletal muscle atrophy, characterized by the loss of muscle mass and function, can result from disuse, aging, disease, drug. Exercise preconditioning—a form of exercise training performed before these harmful threats—induces notable remodeling and extensive biochemical adaptations in skeletal muscle, creating a protective phenotype in muscle fibers, and thus serving as an effective intervention for preventing skeletal muscle atrophy. Here, we review the current understanding relating to how exercise preconditioning protects skeletal muscle from damage caused by inactivity, sarcopenia, disease, or pharmacological intervention, with an emphasis on the cellular mechanisms involved. Key mechanisms highlighted as making a significant contribution to the protective effects of exercise on skeletal muscle fibers include mitochondria; the expression of cytoprotective proteins such as HSP72, SOD2, SESN2, PGC-1α and AMPK; and the regulation of oxidative stress. These findings underscore the potential of exercise preconditioning as a non-pharmacological intervention for preserving muscle mass and function, as well as preventing muscular atrophy, ultimately improving the quality of life for at-risk populations.